Establishing a Positive Clinical Learning Environment in the Surgery Core Clerkship: A Video-Based Mistreatment Curriculum - Laura Mazer; Cara Liebert; Sylvia Bereknyei Merrell; Dana Lin; James Lau (Association of American Medical Colleges, 2015)
Abstract Medical student mistreatment has been a pervasive problem in the educational literature since the 1980s. In the 2014 Association of American Medical Colleges (AAMC) Graduation Questionnaire, excluding reports of public embarrassment, 39.9% of graduating medical students reported experiencing some form of mistreatment during medical school. This video-based module was designed to establish a positive clinical learning environment and reduce medical student mistreatment in the surgical core clerkship. The program consists of a preclerkship session to set expectations and an end-of-clerkship debriefing. The program's objectives include discussing preexisting expectations of the clerkship, creating a consensus definition of mistreatment, and identifying available resources for responding to mistreatment if it occurs. Both sessions are based around short trigger videos designed to spark discussion. This program has been implemented at one surgical clerkship program for over a year, and elements of the program have been used in other clerkship programs, including emergency medicine and obstetrics and gynecology. Eighty-four students (N = 89, 94% response rate) who participated in the mistreatment program between March 2014 and February 2015 completed the anonymous, electronic, end-of-curriculum survey. Students rated each session on a 5-point Likert scale (1 = poor, 5 = outstanding). Mean (standard deviation) ratings for the mistreatment program sessions during the first and last weeks of the clerkship were 4.04 (0.90) and 4.30 (0.76), respectively. The majority of students rated the initial mistreatment session as "excellent" or "outstanding" (78%), with 90% rating the second session as "excellent" or "outstanding." In the open-ended survey, 100% of student responses were coded as "positive" by two independent reviewers.